17α‐Ethynylestradiol‐induced changes in Brassica rapa during the seedling growth stage. Issue 2 (28th March 2022) - Wijewardana, Chathurika; Gonzales, Annelise K.; Vogel, Charlotte M.; Martinez, Nicole E.
Abstract: Estrogens and estrogen‐like compounds are considered contaminants of emerging concern due to their endocrine disrupting capability and potential to build up in soil and aquatic environments, although little is known about the effects of estrogenic compounds on plant life. This research aims to understand the effect of the synthetic hormone 17‐α ethynylestradiol (EE2) on Brassica rapa L. (field mustard) root and shoot vigor at the seedling stage. Endpoints considered included: plant height; root, shoot, and total dry biomass; number of leaves and inflorescences; leaf carbon and nitrogen; root growth traits (length, surface area, diameter, and volume); and root developmental parameters (tips, forks, and crossings). Tukey's method for multiple comparisons was used to determine the significance of pairwise differences between treatment means for each endpoint. 17‐α Ethynylestradiol acted generally as a biostimulant at the concentrations considered (0, 0.5, 1, 5, 10, and 15 μg L −1 ), with the most pronounced differences occurring in seedlings treated with 1 μg L −1 EE2. Although number of leaves and biomass appeared to be inhibited at EE2 concentrations of ≥5 μg L −1 and ≥10 μg L −1, respectively, all other traits in estrogen‐treated plants were similar or improved compared with the control plants. Study results suggest that at certain concentrations, EE2 contributes to more structured root systems, triggering vigorous plant development that may potentially enhance a successful seedling establishment. Core Ideas: Field mustard seedlings were exposed to the synthetic hormone EE2. 17‐α Ethynylestradiol functioned as a biostimulant with the most pronounced effects observed at 1 μg L −1 . Most plant traits were similar or improved compared with controls up to 15 μg L −1 . Results inform management of crop growth in urban agricultural fields.